The Socio-Economic Impact of the Dui’ Pappenre’ Tradition (Gift Money) on the Household Economic Resilience of the Bugis Community - Riswan Riswan; Asriadi Arifin; Irwandi Irwandi (Transpublika Publisher, 2025)
Dui’ Pappenre’ in Bugis marriage holds a negative stigma among the community, but from an Islamic economic perspective, Dui’ Pappenre’ becomes an instrument that can stimulate a man’s economic and mental circulation. This study aims to analyze the socio-economic impact of the Dui’ Pappenre’ tradition while examining its influence on the economic resilience of Bugis Muslim households. This study applies a qualitative descriptive design through an ethnographic approach and an interpretive paradigm to dissect the reality of the research object naturally. Through an ethnographic approach, this study seeks to explore a comprehensive explanation of the socio-cultural phenomenon of Bugis marriage based on the perspectives and direct experiences of the research subjects. Data were collected through observation techniques and in-depth interviews, which were strengthened by the results of previous studies as secondary data. Furthermore, the data were analyzed using the Miles and Huberman model which includes the stages of data condensation, data presentation, and drawing conclusions. The results show that the high levels of dowry and Dui’ Pappenre’ are sometimes seen as obstacles to marriage. However, substantively, it is a cultural symbolization that reflects the sacredness of marriage for the Bugis community. In Islamic economics, this phenomenon is viewed as an effort to fulfill the common good (maslahah) and distribute economic prosperity collectively. This research projects that if managed with principles of justice and appropriate financial protection, Dui’ Pappenre’ can transform into a pillar of resilience for the economic stability of Muslim households in the future.